Treatment Of Fractures of The Leg Bones and Polarographic Control of Blood Supply to Tissues - O. N. Abdulazizov (Genius Journals, 2024)
Using the method of polarography with open needle sensors and transcutaneous polarography, various groups of patients with fractures of the lower leg bones were examined during the treatment. It was found that with closed helical fractures, as the severity of the injury increases, the rate of capillary blood flow and oxygen utilization in the tissues decreases. With closed helical fractures with displacement of fragments up to 75% of the diameter of the bones increase, and with large displacements, as well as with comminuted and open fractures, muscle elasticity, volumetric blood flow velocity of the leg and oxygen tension in the tissues decrease
Keywords: blood supply to the lower leg; treatment of fractures; tissue oxygenation